Analisis Pendapatan Usahatani Garam di Kecamatan Darul Aman Kabupaten Aceh Timur - Muna, Hayatul; Alham, Fiddini; Mahyudin, Thursina (Jurnal Penelitian Agrisamudra, 2024)
The aim of this research is to analyze the income of salt farming in Darul Aman District, East Aceh Regency. The method used in this research is the survey method and simple random sampling method. From the results of data analysis, it was found that the average production cost for making salt was Rp. 5,611,057/Month. The average production and income from making salt is IDR. 7,448,000/month. The average net income from making traditional salt is IDR. 1,811,648/ month. The result of the B/C Ratio = 1.36. Because the B/C Ratio value is greater than 1, it is said that the salt business is feasible to carry out.